Knowledge about triatomines and Chagas disease in inhabitants of the municipality of Barra, Bahia (Research, Society and Development, 2022)
Chagas disease is one of the main neglected endemias in Latin America, caused by the flagellated protozoan Trypanosoma cruzi, transmitted by triatomins (haematophagous hemipters) popularly known as "barber". Epidemiological Surveillance and community participation work in the control and prevention of this disease. This study aimed to evaluate the knowledge, perception and practices of residents of the municipality of Barra, Bahia about Chagas disease. Popular knowledge was evaluated through the online application of a semi-structured questionnaire. The 62 residents interviewed claim to know the vector, as well as its association with the transmission of Chagas disease, however, 31.8% report discarding the insect incorrectly. The recognition of the vector occurred through images containing predatory hemipters, phytophagus and haematophagus (Sordid Triatoma), where 95.2% correctly identified the specimen. When asked about clinical healing, 74.2% are unaware of this possibility. It is believed that the knowledge of the Barrense population is limited, there is seen that 32.3% of respondents reported not knowing about the disease control service in the municipality, as well as, 37.1% reported that they do not carry out preventive measures in the homes, although there is a high frequency of triatomins in the region. The operation of the municipal Epidemiological Surveillance together with community participation is indispensable in the fight against Chagas disease. Our results have important implications in the development of future educational materials and campaigns involving children, adolescents, young people and adults in conjunction with the city's education and health professionals in promoting Chagas disease.